2013
DOI: 10.1097/scs.0b013e3182800f23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pigments and Pigmenting Methods on Color Stability of Different Silicone Maxillofacial Elastomers After 1-Year Dark Storage

Abstract: Significant color changes were observed in both pigmented and unpigmented specimens, which were stored in dark environment and not exposed to sunlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…It was concluded that, after 6000 h of dark storage, the colour change becomes perceptible regardless of vulcanization temperature and molding-stone colour. This result provides further evidence for the intrinsic colour degradation of maxillofacial silicone elastomers, which has also been demonstrated by Hatemleh et al, Polyzois et al, Haug et al, and Bankoglu et al [24, 25, 29, 39].…”
Section: Discussionsupporting
confidence: 83%
“…It was concluded that, after 6000 h of dark storage, the colour change becomes perceptible regardless of vulcanization temperature and molding-stone colour. This result provides further evidence for the intrinsic colour degradation of maxillofacial silicone elastomers, which has also been demonstrated by Hatemleh et al, Polyzois et al, Haug et al, and Bankoglu et al [24, 25, 29, 39].…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the material used in this study can withstand color change against natural weathering conditions and we also recommend using the neutral soap type that was used in this study. 8,10,12 Several authors suggested that color change may undergo with time without any external factor, which may be attributed to the additional cross-linking caused by continued chemical polymerization of the elastomer or by side reactions among impurities present within the silicone. Therefore it is worthy that the clinician must know the pigments, the coloration methods, and polymerization procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Also the nonstop release of sub-products throughout this continuous polymerization process not only causes dimensional alterations of the silicon material but also chromatic pattern variations. 10,16 Color deterioration of the maxillofacial silicone prosthesis is attributed to the collective effect of numerous aspects such as environmental exposure, UV radiation, humidity, air pollutants, the method of disinfection and exposure to facial secretions as perspiration. On the other side internal factors include silicone composition, mode of curing, degree of cross-linking, extrinsic and intrinsic stains used; all these factors have a significant role in preserving or deteriorating the color of the silicone prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer yandan bu dıĢ etkilerin hiç birine maruz kalmayan karanlık ortamda, ısı ve nem koĢullarının optimal olduğu koĢullarda bekletilen silikon elastomerlerin de polimer yapısında devam eden çapraz bağlantı reaksiyonları ve pigmentlerin etkileĢimleri sebebiyle bir miktar renk değiĢimi gösterdiği bildirilmiĢtir. 35 GüneĢten gelen UV ıĢınları ve materyalin yapısal reaksiyonları sebebiyle bozulma hasta ve hekim tarafından kontrol edilmesi mümkün olmayan sebepler iken protez dezenfeksiyonunda kullanılan yöntemler arasında materyali en az etkileyeni seçmek, yapımı zahmetli ve maliyetli olan bu protezlerin ömrünü uzatmak için önemli bir konudur. Bu sebeple çalıĢmada bu protezlerin dezenfeksiyonu için sıklıkla kullanılan yöntemlerin renk değiĢimi ve yüzey pürüzlülüğü üzerindeki etkisi incelendi.…”
Section: Tartiġmaunclassified